Deceptive apparatus: Foucauldian perspectives on law, authorised crime and the rationalities of undercover investigation. Issue 2 (2nd April 2016) - Murphy, Brendon
ABSTRACT: Investigation of crime is central to the function and purpose of law enforcement. Contemporary investigation depends on a sophisticated arsenal of theories and techniques interacting with law and its institutions in a variety of ways, including authorised unlawful activity. Drawing on Foucault, this article re-imagines the investigation and associated legal architectures as apparatus; a rationality and strategy of governance shaped by intersecting knowledge formations. The paper considers the key characteristics of investigation and its relationship with law, concluding that investigations practices are a form of apparatus, and that aspects of these practices are grounded in a theological dynamic based on surveillance.